Surdo-Terena: a (in)existência de sujeitos (s)em política(s) linguística(s) - Michelle Sousa Mussato (2022)
By taking a look at the speeches of deaf subjects of the Terena ethnicity, a diversity of representations, constructions, displacements and identity traits crossed by knowledge-power relations is presented. I see that the Terena deaf are placed on the margins of the hegemonic society in a double exclusion, since there is no discursivity that legitimizes them, that inscribes them as deaf Indians, urging me to start a research under the hypothesis that the lack of visibility to the linguistic policies that contemplate the socio-historical and cultural aspects of the Terena deaf, via language, reinforce the coloniality marks of the subjects, in the face of the interposition of the culture(s) and language(s) of the other(s). Thus, this research has the general objective of understanding how the (lack of) language policy affects the subjective constitution of Terena deaf subjects. Specifically, we are interested in investigating the crossing of linguistic policies that permeate the process of identity constitution of the Terena deaf; to identify the discursive events that denote the process of (in)existence of the deaf indigenous of the Aldeia de Cachoeirinha facing the representations of the subject and the educational process; to problematize the devices of power-knowledge and the strategies of (de)coloniality from the interpretative gesture of the representations of the self and the other of/about the Terena deaf. Therefore, we list a transdisciplinary theoretical plurality that, among the concepts worked, I highlight the (re)signification of subject, discourse, discursive formation, interdiscourse, discursive memory, heterogeneity from authors that corroborate and constitute the Discourse Analysis of French origin. (FOUCAULT, 1987; 1990; 1996; 1997; 1999a and b; 2005; 2007; PÊCHEUX, 1990, 1997, 2006; CORACINI, 2003, 2007, 2010; AUTHIER-1990 1998), or Foucault's archeogenealogical method (1990) and southern studies, from the perspective of disobedience/epistemic transgression, which aggregate local knowledge by providing a counter-hegemonic critical reflection on the processes of (de)coloniality, abyssality (SOUZA-SANTOS, 2002, 2008, 2010; CASTRO-GOMÉZ, 2005, 2007; MIGNOLO, 2003, 2005; QUIJANO, 2007) in the face of translingual (CANAGARAJAH, 2004, 2011, 2013) and transcultural (COX, ASSIS) practices. PETERSON, 2007; ORTIZ, 1983) immers as in this transterritorial dwelling (HAESBEART, MONDARDO, 2010) to which the deaf Indian of the Terena ethnicity is. The corpora, in this way, consists of interviews granted by deaf (two) and hearing (three) indigenous people who participate in this process (cultural, educational and institutional).